Medical riding as mean of physical rehabilitation of children with a cerebral paralysis - Dobrowolska M.V (Kharkov National Pedagogical University, 2010)
Influence of the medical riding is appraised on the functional state of locomotorium of children. In an experiment took part 20 children with a cerebral paralysis in age 9-10 years. To the standard program of physical rehabilitation the medical riding is additionally included. Riding was used 3 times for a week, by a course for 40 procedures. The amount of exercises and concrete types of exercise get out in every case individually. In an experimental group in blocks «crawl» a middle result grew on 3,2 marks, «seat» - on 5,2 marks, «walking» - on 3,4 marks, «on one leg» - on 1,35 marks. Middle difference between the second testing indexes on blocks was higher in an experimental group: an estimation is a «crawl» - higher on 1,4 marks, «seat» - on 2,6 mark, «walking» - on 2,3 mark, «on one leg» - on 1,1 mark.